2019
DOI: 10.1021/acschemneuro.8b00676
|View full text |Cite
|
Sign up to set email alerts
|

Increased Secondary Nucleation Underlies Accelerated Aggregation of the Four-Residue N-Terminally Truncated Aβ42 Species Aβ5–42

Abstract: Aggregation of the amyloid-β (Aβ) peptide into plaques is believed to play a crucial role in Alzheimer's disease. Amyloid plaques consist of fibrils of full length Aβ peptides as well as N-terminally truncated species. β-Site amyloid precursor protein-cleaving enzyme (BACE1) cleaves amyloid precursor protein in the first step in Aβ peptide production and is an attractive therapeutic target to limit Aβ generation. Inhibition of BACE1, however, induces a unique pattern of Aβ peptides with increased levels of Nte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…To date, four BACEi drugs evaluated in late‐stage trials showed cognitive worsening during the treatment 41. One potential explanation for this finding is that alternate forms of N‐terminally truncated Aβ may be produced from APP in a β‐secretase–independent pathway, as recently reported by two groups 52–54. These alternate Aβ peptides were reported to form highly toxic Aβ oligomers 54.…”
Section: Alz‐801 Program Provides Effective Test Of Amyloid Hypothesimentioning
confidence: 81%
See 2 more Smart Citations
“…To date, four BACEi drugs evaluated in late‐stage trials showed cognitive worsening during the treatment 41. One potential explanation for this finding is that alternate forms of N‐terminally truncated Aβ may be produced from APP in a β‐secretase–independent pathway, as recently reported by two groups 52–54. These alternate Aβ peptides were reported to form highly toxic Aβ oligomers 54.…”
Section: Alz‐801 Program Provides Effective Test Of Amyloid Hypothesimentioning
confidence: 81%
“…41 One potential explanation for this finding is that alternate forms of N-terminally truncated A may be produced from APP in a -secretase-independent pathway, as recently reported by two groups. [52][53][54] These alternate A peptides were reported to form highly toxic A oligomers. 54 Therefore, A oligomer assays for A 40 and A 42 in BACEi studies may not correlate with clinical benefit for this class of drugs.…”
Section: Several Bacei Treatments Have Been Evaluated In Patients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial increase in aggregate mass was measured through linear fits to the early points of the aggregation process, Fig. S3a, S3c, S3e and S3g [29,30]. The estimated elongation rate constant for PSMα1 and PSMβ2 were found to be 0.2 mM/h 2 and 0.5 mM/h 2 respectively, differing by a factor of ~2, which is insignificant.…”
Section: Elongation Rates Differ By a Factor Of 1000 Between Fastest mentioning
confidence: 99%
“…To gain insight into the composition of the soluble aggregates responsible for the observed membrane permeabilisation, we employed an Aβ-specific antibody (Nb3) previously shown to counteract the toxicity induced by soluble aggregates of full length as well as N-terminally truncated Aβ both in vitro 16,23 and AD CSF 19 . We found that Nb3, which recognises amino acids 17-28 of the Aβ sequence, was able to significantly reduce the aggregate-induced membrane permeabilisation for both AD and MCI ( Fig.…”
Section: Soluble Amyloid-beta Aggregates Present In Ad and MCI Csf Armentioning
confidence: 99%